THE PLACE AND SIGNIFICANCE OF THE CRADLE IN THE UZBEK FAMILY - Matkarimova NilufarMaxsudovna; Matkarimova NilufarMaxsudovna (International Multidisciplinary Journal for Research & Development, 2024)
This article is about the unique customs, traditions, and values of the ceremonies held and circumcision weddings in Khorezm, their versatility, longevity, and the fact that they are not carried out by a few individuals, but by many. , about concepts such as the rich cultural and spiritual heritage of the nation, its ethno-territorial and ethno-cultural uniqueness, rituals, traditional ceremonies, spiritual and moral values, kinship relations information provided.